A REVIEW ON SUPERSONIC PARTICLE DEPOSITION AS POTENTIAL SOLUTION FOR AIRCRAFT METAL MOLD REPAIR - Omar, Nooririnah; Abdullah, Rohana; ABD RAZAK , JEEFFERIE; Mustafa, Nuzaimah (Global Engineers and Technologists Review, 2013)
The global Maintainence , Repairing and Overhaul (MRO) services industry is forecast to be worth US$65 billion by 2020. Malaysia plans to become a regional hub for aircraft maintenance and repairs. The country was currently ranked fifth in Asia and tenth in the world in terms of aircraft maintenance, repair and overhaul. Maintenance or repair technique play a major role in increasing useful life of the aerospace part and it increase the confident level of the user. Supersonic particle deposition has attracted serious attention because it unique thick dimensional restoration properties can be obtained by the process that is not achievable by thermal spraying. This uniqueness is due to the fact that dimensional restoration deposition takes place without exposing the spray or substrate material to high temperature and its ability to perform a bonding with the underlying material without the creation of heat affected zones which are typical of other deposition processes, thermal spray and are undesirable in many structural applications. This paper is an outcome to discuss supersonic particle deposition process as potential repair technique for aircraft metal mould, which is widely acclaimed for and on top of that, re-use of material will contribute to cost saving and in-haze the environment. Keywords: Cold Spray, Supersonic Particle Deposition, Repair, Metal Mould, Aircraft.